Pemanfaatan Digital Marketing dan Pengelolaan Keuangan Pada Toko Bahan Kue - Ni Luh Ratniasih; Dwi Haryadi Nugraha (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
Competition in the cake and bread business is quite tight, this is marked by the emergence of the same business, and the increasing variety of breads and cakes offered. The development of culinary business is also seen from the number of shops opened baking cake ingredients. Partners in this service activity are a cake ingredients shop and sell pastries located in the Denpasar city market area. The name of the partner shop is "Annika Shop" which is located at Jalan Trenggana, No. 2 Penatih, East Denpasar. The shop owner named Ibu Ni Gusti Ayu Anggreni is assisted by 2 employees. In this service activity, the partner's problem handled is the lack of maximum product marketing and financial management activities are not carried out so that the loss / profit of the business can be less known and measured. From these main problems, a solution to this community service is provided, namely training in the use of digital marketing to introduce business to the wider community and financial management training. Achievement indicators are able to introduce business partners to the wider community so as to increase partner income up to 50% from before the training. Able to increase the ability and knowledge of partners in financial management up to 100%.Competition in the cake and bread business is quite tight, this is marked by the emergence of the same business, and the increasing variety of breads and cakes offered. The development of culinary business is also seen from the number of shops opened baking cake ingredients. Partners in this service activity are a cake ingredients shop and sell pastries located in the Denpasar city market area. The name of the partner shop is "Annika Shop" which is located at Jalan Trenggana, No. 2 Penatih, East Denpasar. The shop owner named Ibu Ni Gusti Ayu Anggreni is assisted by 2 employees. In this service activity, the partner's problem handled is the lack of maximum product marketing and financial management activities are not carried out so that the loss / profit of the business can be less known and measured. From these main problems, a solution to this community service is provided, namely training in the use of digital marketing to introduce business to the wider community and financial management training. Achievement indicators are able to introduce business partners to the wider community so as to increase partner income up to 50% from before the training. Able to increase the ability and knowledge of partners in financial management up to 100%.